Changes of grip strength, articular cartilage and subchondral bone in monoiodoacetate-induced osteoarthritis in rats - Ekeuku, Sophia Ogechi; Fairus Ahmad,; Chin, Kok-Yong (Universiti Kebangsaan Malaysia, 2022)
Osteoarthritis is a degenerative disease affecting articular cartilage among the elderly. The intra-articular monoiodoacetate injection is one of the most widely used methods to induce osteoarthritis in animals. While the effects of monoiodoacetate on cartilage are well-characterized, its effects on subchondral bone remodeling are less studied. The purpose of this study was to determine the changes of the grip strength, articular cartilage structure and subchondral bone remodeling in monoiodoacetate-induced osteoarthritis in rats. Three-month-old male Wistar rats were assigned to normal control (n=6) and osteoarthritis group (n=6), which received intra-articular injection of 4 mg/50 μL monoiodoacetate solution once at the left knee of hindlimb. The rats were monitored for four weeks. The grip strength test was performed before injection and every week after injection. After four weeks, the femurs with intact cartilage were harvested for histomorphological analysis. Grip strength was reduced significantly in the osteoarthritic rats compared to the normal rats (p<0.05). Food intake was reduced significantly one week following monoiodoacetate-induction (p<0.05), but it stabilized afterwards. Monoiodoacetate injection increased cartilage erosion and osteoclast number in the subchondral bone of the osteoarthritic rats compared to the normal rats (p<0.05). However, it did not affect body weight, subchondral bone osteoblast activity, mineralization and microstructure of osteoarthritic rats (p>0.05). As a conclusion, monoiodoacetate-induced osteoarthritis affects the cartilage and increases osteoclast formation in the subchondral bone of rats.